Reification of the Signified and Consumerization of Wedding Receptions “Sintê Mungêrjê” In The Gayo Lôt Society In Central Aceh District - Bakti, Indra Setia; Nirzalin; Abidin (Sodality: Jurnal Sosiologi Pedesaan, 2020)
Gayo customs emphasizes the values ​​of mutual cooperation and religiosity. The ritual of "sintê môrep” illustrates this reality. However, consumerism has threatened an identity and social integration, such as at wedding receptions. This study employs a qualitative approach to explore the changing process of the kenduri "sintê mungêrjê" into a party culture in wedding receptions at the Gayo Lôt community. The study reveals reification has encouraged changes in the meaning of Gayo traditions. The shift occurred from the denotative level to the connotative level. The consumption culture of weddings developed as a design of consumerization by wedding organizer in Central Aceh Districtand was supported by party simulations through television and social media. Simulacrum works because Gayonese prefer tocall "party" to "sintê mungêrjê" (the local term). The party culture was triggered by the weakening of the village structure supported by degradation of understanding of the Gayo customs, the Gayo language that hasgradually been abandoned by native speakers, urban development, information technology, the strengthening of money logic, the changing in the type of work from agrarian to formal, and cultural assimilation and acculturation.